Frequency of ABO blood system type alleles in students of UIN Sunan Ampel Surabaya - Kautsar, Radinal; Putri, Siti Aisyah Bisri; Azzhahara, Nabillah Ayu; Aini, Humayra Qurrata; Pradiptaadi, Brian Pramana Aprilio; Nabila, Salsa; Arrohmah, Robiatush Sholichah; Rachmawati, Yuanita (Genbinesia Journal of Biology, 2022)
The commonly used human blood group system is the ABO system. Determination of blood group is important in blood transfusion activities. The purpose of this study was to determine the frequency of the ABO blood group system and the frequency of the ABO blood group allele in students of the Biology and Science Education study program at UIN Sunan Ampel Surabaya. Determination of blood group was carried out by the Slide Test method which was carried out randomly with a sample of 90 people. Determination of blood group is done by the principle of agglutination that occurs between antigens and antibodies. The results showed the frequency of blood group ABO system: A (20%); B (24%); AB (10%); O (46%). IA allele frequency (0.13); IB (0.07); IO (0.8). The proportion of the highest frequency of blood type is blood type O. These results indicate that the distribution of blood type O among students at UIN Sunan Ampel Surabaya is relatively the same as the results of other studies conducted in Indonesia.